The new financial deal understanding the Dodd-Frank Act and its (unintended) consequences - Skeel, David A., 1961- (Wiley, 2011)
"What can we expect from our era's New Deal? To answer this question, The New Financial Deal will begin with an inside account of the legislative process, then outline and access its key components: the new framework for regulating derivatives, the regulation of banking and systemic risk, and the new resolution regime. It will explain the implications of the new framework, and propose correctives that would better align its ostensible objectives--such as preventing future bailouts--with the new regulatory structure. The legislation's key theme is government partnership with and regulation of large concentrated institutions in order to reduce their risk and manage their failure. In place of the decentralized pre-crisis regulation of derivatives, the new legislation will require that most derivatives be cleared through a clearing house and traded on exchanges. The stability of the derivatives market will therefore depend on a small number of potentially enormous clearing houses. For large financial institutions that encounter financial distress, the legislation gives bank regulators sweeping new authority to step in and take over the institution. Regulators, rather than negotiations among the parties themselves, will determine the outcomes. These epochal reforms are posed to change Wall Street forever, but whether they help to regulate supermarket banks or create even more moral hazard is worthy of serious debate."--